PENGARUH KINERJA GURU PKN DAN IKLIM BELAJAR TERHADAP MOTIVASI BELAJAR SISWA - Yogi Nugraha (Wahana Karya Ilmiah Pendidikan, 2020)
Abstract. “Influence Civics Teacher Performance and Learning Against Climate Student Motivation” This study examines (1) Effect of Civics teacher performance to student motivation, (2) influence of climate on the students motivation to learn, and (3) Effect of Civics teacher performance and learning climate on student motivation.The study uses a quantitative approach with survey method. Collecting data using a questionnaire study. The population is a class VIII. The number of schools included in the sample amounted to 2 schools. Number of class VIII students of both schools as many as 572 respondents. The technique of taking with multistage random sampling were then taken 10% of the total population of each school class VIII, thus amounted to 57 respondents at 95% level of truth.The results showed that (1) Performance Civics teacher effect on student motivation. (2) Climate learn affect motivation for students, and (3) Performance Civics teachers and learning climate at the same time influence the students' motivation. Keyword: Civics Teacher Performance, Learning Atmosphere, students' motivation. Abstrak “Pengaruh Kinerja Guru PKn dan Iklim Belajar Terhadap Motivasi Belajar Siswa” Penelitian ini mengkaji tentang (1) Pengaruh kinerja guru PKn terhadap motivasi belajar siswa, (2) Pengaruh iklim belajar terhadap motivasi belajar siswa, dan (3) Pengaruh kinerja guru PKn dan iklim belajar terhadap motivasi belajar siswa.Penelitian menggunakan pendekatan kuantitatif dengan metode survey. Pengumpulan data menggunakan kuesioner penelitian. Populasi adalah kelas VIII. Jumlah sekolah yang termasuk dalam sampel berjumlah 2 sekolah. Jumlah peserta didik kelas VIII dari kedua sekolah sebanyak 572 responden. Teknik pengambilan dengan multistage random sampling kemudian diambil 10% dari jumlah populasi kelas VIII setiap sekolahnya, sehingga berjumlah 57 responden pada tingkat kebenaran 95%.Hasil penelitian menunjukkan bahwa (1) Kinerja guru PKn berpengaruh terhadap motivasi belajar siswa. (2) Iklim belajar berpengaruh terhadap motivasi belajar siswa, dan (3) Kinerja guru PKn dan iklim belajar secara bersamaan berpengaruh terhadap motivasi belajar siswa. Kata Kunci (Keyword): Kinerja Guru PKn, Iklim Belajar, motivasi belajar siswa